The Quality of Service in Processing Passports of Indonesian Citizens at the Immigration Office Class I TPI Denpasar - A.A Istri Saraswati; Kadek Wiwin Dwiwismayanti (Westscience Press, 2024)
This study aims to determine the quality of service as well as the supporting and inhibiting factors in passport processing at the Immigration Office Class I TPI Denpasar. Service quality is a dynamic perspective that becomes a public problem of trust and confidence in public service providers. The number of informants in this study were 11 people. This type of research uses descriptive qualitative. Data collection techniques using observation, interview, and documentation methods. The results showed that it has not been achieved optimally seen through the Reliability aspect where when there is a system or network disruption that causes the service process to be inefficient, while the service officer is not reliable and depends on one officer, so that the handling of the problem is gradually over a long period of time, seen from other aspects such as Tangible, Responsiveness, Assurance and Attention (Empathy) has been achieved optimally. At the Immigration Office Class I TPI Denpsar, the supporting factor in service quality is infrastructure facilities, while the inhibiting factor in achieving excellent service is the lack of public awareness.